IMPLEMENTATION OF BIRA BEACH TOURISM SECTOR RETRIBUTION MANAGEMENT POLICY IN IMPROVING REGIONAL ORIGINAL INCOME IN BULUKUMBA REGENCY - Anwar, Putri Ananda; Guntur, Muhammad; Aslinda, Andi; Rukmana, Novayanti Sopia (Universitas Negeri Makassar, 2025)
This study aims to determine the Implementation of the Bira Beach Tourism Sector Levy Management Policy in Increasing Regional Original Income in Bulukumba Regency. This research uses a qualitative approach and produces descriptive data. Data collection was carried out by observation, interview, and documentation techniques. The data was analyzed using qualitative analysis. The results of the study show that the Implementation of the Bira Beach Tourism Sector Levy Management Policy in Increasing Regional Original Income in Bulukumba Regency. based on 6 major variables that must be achieved, namely: Sources and objectives of policy in the tourism government, especially conducting regulations related to beach management and regulating permits and licensing. The objectives of tourism policy are a) Policy sources and objectives to increase the contribution of the tourism sector to the local economy, b) Policy Sources Local governments, tourism agencies, international organizations, and local communities are very important to achieve holistic and sustainable management. C Characteristics Characteristics An effective tourism implementing agency must have the ability to actively involve local communities in coastal management. d) Communication between organizations has a good impact on tourism managers and local governments in Regional Original Revenue, e) The attitude of tourism implementers includes friendliness, professionalism, and responsiveness. In addition, patience is also needed. Facing various kinds of tourists with different characters and needs, f) The economic, social and political environment has an important role in the development of tourism at the level of community participation and lack of knowledge about the procedures for managing tourist attractions. This causes these tourist attractions to not progress and even tend to regress.